2021
DOI: 10.1016/j.fuel.2020.118877
|View full text |Cite
|
Sign up to set email alerts
|

Entropy-scaling based pseudo-component viscosity and thermal conductivity models for hydrocarbon mixtures and fuels containing iso-alkanes and two-ring saturates

Abstract: Entropy-scaling based pseudo-component viscosity and thermal conductivity models for hydrocarbon mixtures and fuels containing iso-alkanes and two-ring saturates. Fuel, 118877..

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Fuel properties are generally known to affect spray atomisation [32,33]. Fuel properties such as viscosity and density have been found to significantly change as a function of injection pressure and liquid temperature, as reported by the relevant experimental and computational studies reported recently in [34][35][36][37][38][39][40][41] which reported variations for pressures as high as 3000 bar and temperatures up to 560 K. The influence of those on the cavitation of multi-component fuel surrogates has also been investigated in [42]; significant variations of the cavitation structures and vapour composition have been reported, with pressure increase to values up to 4500 bar. In addition, fuel composition and the mixing of fuels can be additional influential factors.…”
Section: Introductionmentioning
confidence: 86%
“…Fuel properties are generally known to affect spray atomisation [32,33]. Fuel properties such as viscosity and density have been found to significantly change as a function of injection pressure and liquid temperature, as reported by the relevant experimental and computational studies reported recently in [34][35][36][37][38][39][40][41] which reported variations for pressures as high as 3000 bar and temperatures up to 560 K. The influence of those on the cavitation of multi-component fuel surrogates has also been investigated in [42]; significant variations of the cavitation structures and vapour composition have been reported, with pressure increase to values up to 4500 bar. In addition, fuel composition and the mixing of fuels can be additional influential factors.…”
Section: Introductionmentioning
confidence: 86%
“…Their conception is based only on van der Wall dispersion forces [21], as a consequence, their precision decreases at conditions of strong association between molecules and at high pressure and high temperature (HPHT) conditions [22,23]. Recent works from the author's group report measurements and validated modelling methods predicting the variation of diesel fuel properties at pressures as high as 3000bar and temperatures up to approximately 550K [24][25][26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Another group also proposed a model based on entropy scaling and a four-parameter model to calculate well-characterized hydrocarbon mixtures and fuels at high pressures . In a general way, entropy scaling has been implemented with the equation of state for several industrial applications and not only focused on the petroleum industry. …”
Section: Introductionmentioning
confidence: 99%